Rancang Bangun Sistem Jemuran Pakaian Otomatis Menggunakan Metode Fuzzy Logic - Muchammad Husni; Henning Titi Ciptaningtyas; Adetiya Bagus Nusantara (Operations Excellence: Journal of Applied Industrial Engineering, 2019)
Clothesline clothing is a necessity that must be owned by almost every one. Rain or inclement weather up to now become a key issue for the people that have a clothesline. At the time of the rainy season, the majority of people feel anxious when they're drying the clothes. The anxiety will increase while at the time of drying clothes but concerned are located outside the House and in the House was no person. The genesis of the people so reluctant to open places pakain drying, fearing jemurannya wet exposed to rain water. This research has been made on a prototype automatic clothes clothesline system using microcontroller, Arduino wifi module, a motor with sensors-sensors installed in it. In the logic of determining the weather conditions used fuzzy logic to produce output that is accurate. The prototype architecture is intended to make it easier for people when drying their clothes, so when the rain struck, clothesline clothing can move automatically toward the shade so that her clothes were not wet exposed to rain water. Of all the testing and evaluation that have been carried out, i.e. testing the response of the sensor against rain, tools testing response tool against the light sensor, testing mobile applications in data reading on the sensor and testing system in controlling Clothesline the clothes manually using mobile applications, obtained that the system created has been functioning properly and produce output as expected.